Ultra-large sized graphene nano-platelets (GnPs)incorporated polypropylene (PP)/GnPs composites engineered by melt compounding and its thermal, mechanical, and electrical properties - Jun, Y. S.; Um, J. G.; Jiang, G.; Lui, G.; Yu, A
In this study, polypropylene (PP)/graphene nanoplatelet (GnPs)nanocomposites with very large sized GnPs (?150 ?m)are prepared by melt extrusion followed by injection molding. A number of characteristics including thermal, mechanical, and electrical properties are analyzed. DSC shows that the introduction of GnPs facilitates the crystallization of polymer matrix due to a role of GnPs that serves as seeds for heterogeneous nucleation, and XRD reveals that GnPs have a minor induction effect of ? crystals. Taking advantage of the large size and high aspect ratio of GnPs, a relatively low percolation threshold of ?2.99 vol percent is obtained with highly increased in-plane and through-plane electrical conductivity. The fitting of experimental data to the percolation theory indicates that GnPs are three dimensionally dispersed within the polymer matrix. The composites exhibit relatively limited mechanical enhancement due to compromising of GnPs by the shear force introduced during the compounding process. Overall, the usage of large sized GnPs is clearly beneficial for obtaining high electrical conductivity with a less amount of filler, but an enhanced dispersion of fillers with controlled morphology is required to achieve great physical and mechanical properties of the PP/GnPs composites.
Keywords: POLYMER-MATRIX COMPOSITES (PMCS); ELECTRICAL PROPERTIES; MECHANICAL PROPERTIES; THERMAL PROPERTIES